Manajemen Retribusi Izin Mendirikan Bangunan (IMB) Dalam Meningkatkan Pendapatan Asli Daerah Di Kabupaten Maluku Tengah - Christy Nataliana Mailoa; Stanislaus K. Ohoiwutun; Hengky V. R. Pattimukay (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Management of Building Permit Retribution (IMB) in increasing Local Revenue in Central Maluku Regency. This research is a descriptive qualitative research that aims to analyze the management of Building Construction Permit (IMB) retribution in increasing local revenue in Central Maluku Regency. This research was conducted at the Public Works and Spatial Planning Office of Central Maluku Regency. Primary data was collected through interviews with a number of informants involved in the Management of Building Permit Retribution (IMB) in Central Maluku Regency. The results showed that in the planning stage of building permit retribution (IMB), a target is determined for each year which is influenced by whether or not the target was achieved in the previous year, and in 2022 according to preliminary research the target was not achieved. The reason is that the community is still indifferent about IMB so it must be followed up. In the management team itself, there is a division of tasks for each member, and there is a Standard Operating Procedure (SOP). Although in its implementation, to carry out the SOP, there are still obstacles. As for the fulfillment of the target itself, due to public indifference to IMB, officers must go directly to the scene. In line with this non-compliance, patrols are carried out by a joint team of a number of parties to see and control whether or not there are IMBs on buildings that are being built. And based on local regulations that regulate there are a number of sanctions that can threaten those who violate it. So it is actually necessary to conduct a thorough socialization to the community related to IMB, its management, and other technical matters. .